The role of perception of digital celebrities on live stream shopping intention through social interaction in Indonesia - Mohamad Trio Febriyantoro; Tirta Mulyadi; Eka Hendrayani; Rifadli D. Kadir; Kraugusteeliana Kraugusteeliana; Hersa Farida Qoriani; Achmad Fageh (Cogent Business & Management, 2024)
Despite the growing popularity and commercial potential of live streaming, research on live streaming trade is still in its early stages. Moreover, previous studies have produced inconsistent results regarding the influence of digital celebrity perceptions on consumer shopping intentions. Therefore, this study aims to investigate the antecedents of live-streaming shopping intentions by integrating the Perception of Digital Celebrities with the Uses and Gratifications theory. To achieve this objective, a quantitative approach was employed, and primary data were collected from 504 Indonesian consumers through the distribution of questionnaires. The collected data were analyzed using Structural Equation Modeling based on Partial Least Squares with the aid of SmartPLS 3. The findings of this study suggest that the Perception of Digital Celebrities has a significant effect on consumers' live-streaming shopping intentions. Additionally, Social Interaction was found to have a significant effect on live-stream shopping intention, and Social Interaction was found to mediate the relationship between the Perception of Digital Celebrities and Live-Stream Shopping Intentions.
Keywords: 650; Digital celebrities; social interaction; purchase intention